Evaluation of the anxiolytic activity of ethanolic extract of Ziziphus mauritiana Lam. in Swiss albino mice - Agrawal, Priya; Singh, Talever; Pathak, Devender; Chopra, Himansu; Singh, Kuldeep (Pharmacological research. Modern Chinese medicine, 2024)
Ziziphus mauritiana (Rhamnaceae), also known as Ziziphus jujuba Mill is used in traditional Chinese medicine to treat pain, vertigo, amnesia, and sleeplessness. The objective of this research was to examine the anxiolytic properties of the ethanolic extract of Ziziphus mauritiana (EEZM) in several behavioral paradigms using Swiss albino mice as experimental subjects. after an oral acute toxicity investigation, adult mice were administered EEZM at doses of 200 and 400 mg/kg, orally, and/or diazepam at a dose of 5 mg/kg, intraperitoneally. Subsequently, the mice were exposed to several behavioral assessments. The open-field test included recording the number of square fields crossed while in the light/dark test, the time spent in the light area was calculated and in the Elevated Plus Maze test, the time spent in both the open and closed arms, as well as the number of entries into the open arm were calculated. Furthermore, a comprehensive examination of phytochemicals was conducted. The anti-anxiety efficacy of the ethanol extract of Z. mauritiana was shown to be statistically significant (p < 0.05) as compared to the control group. This was seen by an increase in the average percent of entries and time spent in the open arms of mice treated with a dosage of 400 mg/kg. The administration of the ethanol extract at a dosage of 400 mg/kg demonstrated a significant anxiolytic effect (p < 0.001) in several behavioral tests, including the elevated plus maze, open field test, and light/dark models. The findings of this study indicate that the administration of Z. mauritiana has an anxiolytic effect on mice. Its properties as a novel therapeutic option for the management of anxiety in humans deserve analysis. [Display omitted]